(untitled) (Journal of Enam Medical College, 2012)
Background: The distribution pattern of ABO and Rh-D blood group in our country including the tribal people is not fully established as elaborated and large scale studies have not been carried out on it. Therefore this study was designed to observe the distribution pattern of ABO and Rh-D blood groups among the Garo tribes of Mymensingh and general people of Dhaka city. Objectives: To determine and to compare the distribution pattern of ABO and Rh-D blood groups among the Garo tribal people of Mymensingh and general people of Dhaka city and to compare this distribution between this two groups. Materials and Methods: This observational study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from July 2008 to June 2009. After proper ethical consideration total 900 Garo people of Mymensingh and 784 general people of Dhaka city were included in this study. The Garo localities and the general people of Dhaka city were selected by systematic random sampling. ABO and Rh-D blood groups were determined by the antigen antibody agglutination test of slide method. Chi square statistical analyses were done to compare the results of ABO blood group systems between the Garo people and general people of Dhaka city. Results: This study revealed that there are significant variations in the distribution of ABO and Rh-D blood groups between the Garo tribal people of Mymensingh and the general people of Dhaka city. In this study it was observed that blood group A was apparently predominant in Garo population, while blood group B was predominant in general population (p<0.001), blood group AB and O were almost similar in both groups. Rh typing of the participants reveals that majorities of both groups were Rh positive. Rh negative persons are rare in both populations, but it is extremely rare in the Garo population (0.9%). Conclusion: From the findings of the present study it can be concluded that distribution of ABO and Rh-D blood groups varies between the Garo tribal people and the general people of Dhaka city. DOI: http://dx.doi.org/10.3329/jemc.v1i1.11137 J Enam Med Col 2011; 1(1): 31-35